(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Dental row defects are characterized by the fact that the epidemic process does not have a well-defined periodicity, seasonality, cyclicity. The impossibility of differential diagnosis of dental row defects in clinical manifestations of forms caused the occurrence of tooth row defects not to reflect their actual distribution among the population, making timely adequate management decisions, making it difficult to implement preventive measures. At the same time, the existing material and technical support for laboratory diagnostics of dental row defects did not allow the organization of this monitoring due to the relative costs of screening research methods, the absence of single means of electronic recording of results suitable for all research methods.